Efek Strategi Managerial Pada Kinerja Entitas Usaha Berskala Mikro - Septiyanti, Ratna (E-Jurnal Akuntansi, 2020)
The research empirically examines the effect of managerial strategy on Indonesian micro entities’ performance. The sample consists of 2,527 micro entities at Bandar Lampung city in Indonesia. The result shows that strategy of individually-managed has negative effect on micro entities’ performance. The partnership strategy has a positive effect on its performance, both in enterpreneur and financial partnership. These empirical results indicate that the implementation of good governance on micro entities could increase its performance. The practical implication of this research is as an underlying empirical theory in designing performance measurement system for micro entities. Micro entities should be designed in an agency partnership form to increase its performance.  The policy implication is due to a better lending regulation support. Keywords: Performance Measurement System; Good Governance; Structure; Strategy.